Investigation of glucosuria in children - Konopásek, Patrik; Neuman, Vít; Piteková, Barbora; Zieg, Jakub; Lebl, Jan (Minerva pediatrics, 2025)
Previous reports provided recommendations for familial renal glucosuria diagnosis without complex view on differential diagnosis of glucosuria. The aim of this review was to provide an overview of the causes of glucosuria and to create an evidence-based diagnostic approach for children with glucosuria. We searched the current literature with a focus to identify the possible etiology of glucosuria, gaining insight into the pathophysiology of glucosuria. Urinary glucose is completely reabsorbed in the proximal tubule of kidneys. It only appears in the urine if the plasma glucose concentration exceeds the renal threshold for glucose or in the case of insufficient renal glucose reabsorption. The proteins that provide glucose reabsorption are SGLT2 and SGLT1 - sodium-dependent co-transporters that transport glucose from the lumen into epithelial cells - and GLUT2 - a passive transporter providing facilitative glucose transport from epithelial cells to plasma. Renal glucose reabsorption is affected in case of acquired or inherited complex dysfunction of proximal tubule called Fanconi Syndrome or due to pathogenic variants of genes encoding glucose transporters. Prior to diagnosing any of these, diabetes mellitus must be excluded together with other conditions leading to hyperglycemia. In conclusion, glucosuria is always an abnormal finding. The review provides a simple evidence-based diagnostic approach to navigate the differential diagnosis of glucosuria.
Keywords: Sodium-Glucose Transporter 1; glykosurie; Child; Humans; lidé; Fanconi Syndrome; Glycosuria; glukosa; transportér 1 pro sodík a glukosu; transportér 2 pro sodík a glukózu; renální glykosurie; Diagnosis, Differential; Fanconiho syndrom; Kidney Tubules, Proximal; Sodium-Glucose Transporter 2; proximální tubuly ledvin; Glucose; Glycosuria, Renal; dítě; Glucose Transporter Type 2; přenašeč glukosy typ 2; diferenciální diagnóza